DDM1 and ROS1 have a role in UV-B induced- and oxidative DNA damage in A. thaliana - Qüesta, Julia; Fina, Julieta; Casati, Paula (Frontiers in Plant Science, 2013)
Absorption of UV-B by DNA induces the formation of covalent bonds between adjacent pyrimidines. In maize and arabidopsis, plants deficient in chromatin remodeling show increased DNA damage compared to WT plants after a UV-B treatment. However, the role of enzymes that participate in DNA methylation in DNA repair after UV-B damage was not previously investigated. In this work, we analyzed how chromatin remodeling activities that have an effect on DNA methylation affects the repair of UV-B damaged DNA using plants deficient in the expression of DDM1 and ROS1. First, we analyzed their regulation by UV-B radiation in Arabidopsis plants. Then, we demonstrated that ddm1 mutants accumulated more DNA damage after UV-B exposure compared to Col0 plants. Surprisingly, ros1 mutants show less CPDs and 6-4PPs than WT plants after the treatment under light conditions, while the repair under dark conditions is impaired. Transcripts for two photolyases are highly induced by UV-B in ros1 mutants, suggesting that the lower accumulation of photoproducts by UV-B is due to increased photorepair in these mutants. Finally, we demonstrate that oxidative DNA damage does not occur after UV-B exposure in Arabidopsis plants; however, ros1 plants accumulate high levels of oxoproducts, while ddm1 mutants have less oxoproducts than Col0 plants, suggesting that both ROS1 and DDM1 have a role in the repair of oxidative DNA damage. Together, our data provide evidence that both DDM1 and ROS1, directly or indirectly, participate in UV-B induced- and oxidative DNA damage repair.